PENGARUH TEMAN SEBAYA TERHADAP MOTIVASI BELAJAR SISWA KELAS XII IPS SMA ISLAM HARUNIYAH PONTIANAK - Yuliana Hairunnisa, Isti (Tanjungpura University, 2018)
The research aimed at finding out the effect of peers on motivation to learn for students in grade XII of Social Programme in SMA Islam Haruniyah Pontianak. It is hoped that the result can be a good information for school especially teachers to improve their students’ motivation in learning, motivate their students by a good approach, and motivate among students in learning. The research employed quantitative descriptive methodology by having 64 students of grade XII in social programme as participants of the research using simple random sampling. The data for peers and learning motivation were taken by a questionnaire. Simple linear regression methodology was applied to test the statistical data. The research findings showed that most peer students of grade XII were good and 80,7% of students had low motivation to study. The peers have given significant influence on learning motivation of students and have given positif relation by 78,9%. It can be concluded that the good peers have given positive effect on learning motivation of students of grade XII of Social Programme of SMA Islam Haruniyah Pontianak, on the contrary the bad peers also have decreased motivation of other students to learn.